The role of atropine in carotid stenting of recurrent stenosis after eversion endarterectomy - Demirel, Serdar; Attigah, Nicolas; Bruijnen, Hans; Hoffmann-Wieker, Carola Marie; Böckler, Dittmar (Journal of vascular surgery, 2015)
Objective - The value of prophylactic atropine use during carotid artery stenting (CAS) in primary carotid stenosis to prevent procedural hemodynamic depression is well accepted. However, its impact in case of recurrent stenosis after eversion carotid endarterectomy (E-CEA), which is known to be associated with decreased baroreflex function due to discontinuation of the carotid sinus nerve, has not been investigated so far. - Methods - The influence of angioplasty in the carotid bulb on intraprocedural and periprocedural hemodynamic changes (heart rate [HR], systolic blood pressure [SP], and diastolic blood pressure [DP]) of 38 CAS procedures (primary stenosis group, n = 16; post-E-CEA recurrent stenosis group, n = 22) was analyzed retrospectively. A single dose of 0.5 mg of atropine was administered in all cases immediately before angioplasty. Periprocedural vasoactive management was documented. Within-group differences were analyzed by the nonparametric Friedman test with pairwise comparisons following the method of Conover. - Results - Intraprocedural within-group comparison between the median of the 15-minute period before angioplasty and each of three single measure points with 5-minute intervals after angioplasty showed a significant decrease in almost all measures for the primary stenosis group (HR: P = .002, .0008, .08; SP: P = .005, .01, .01; DP: P = .04, .04, .01) and the opposite for the post-E-CEA stenosis group (HR: P < .0001, <.0001, <.0001; SP: P = .04, .03, .05; DP: P = .23, .06, .005). Whereas in comparison to baseline (day of admission), patients with primary stenosis showed a significant periprocedural decrease in HR (recovery room, P < .0001; 6-24 hours, P = .0012; 25-48 hours, P = .014) and SP (recovery room, P < .0001; 6-24 hours, P < .0001; 25-48 hours, P < .0001), patients with restenosis after E-CEA revealed no significant changes with the exception of increased HR between 6 and 24 hours and decreased DP in the recovery room. - Conclusions - The application of atropine during CAS for recurrent carotid stenosis after prior E-CEA might not be necessary.
Gesehen am 12.01.2021
Available online 31 July 2014